2019
DOI: 10.1155/2019/5095934
|View full text |Cite
|
Sign up to set email alerts
|

Application Value of Magnetic Resonance Perfusion Imaging in the Early Diagnosis of Rat Hepatic Fibrosis

Abstract: Objective. To assess the application value of perfusion-weighted imaging (PWI) in early diagnosis, quantitation, and hepatic fibrosis staging by analyzing the related parameters in hepatic fibrosis. Methods. A total of 60 rats were randomly divided into the hepatic fibrosis and control groups, and carbon tetrachloride (CCL4) was used to establish the liver fibrosis model. All rats underwent PWI examination, and the trend of the time-signal intensity curve (TIC, automatically generated by the software) was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…These pathological changes are aggravated with the progression of liver fibrosis; and thus, TPP was found to gradually increase and show significant differences in each stage of liver fibrosis. Our results were consistent with the study using rat liver fibrosis model conducted by Fan et al [ 42 ]. They showed that TTP and mean transit time values were positively correlated with hepatic fibrosis stage via Pearson's correlation analysis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These pathological changes are aggravated with the progression of liver fibrosis; and thus, TPP was found to gradually increase and show significant differences in each stage of liver fibrosis. Our results were consistent with the study using rat liver fibrosis model conducted by Fan et al [ 42 ]. They showed that TTP and mean transit time values were positively correlated with hepatic fibrosis stage via Pearson's correlation analysis.…”
Section: Discussionsupporting
confidence: 94%
“…Our results indicated that TTP is the most important MR-PWI semi-quantitative parameter for the diagnosis of liver fibrosis with a Youden index of 0.85. Previous study showed that PWI perfusion parameters, especially TTP and mean transit time reflected the degree of hepatic fibrosis [ 42 ]. Since hepatic sinus capillarization and collagen depositions around the hepatic sinus and extravascular space can lead to a prolonged strengthening peak time of contrast agents, more severe liver fibrosis resulted in a longer TTP with a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic sinusoid is the narrowest vascular structure within the liver and is the principal site of blood flow regulation. Hepatic sinusoidal capillarization, characterized by gradually shrinking fenestrae on the surface of liver sinusoidal endothelial cells (LSECs) and forming of an organized basement membrane, is an initial pathologic change associated with liver fibrosis [ 24 ]. Capillary sinusitis is a gradual process.…”
Section: Hepatic Sinusoidal Capillarizationmentioning
confidence: 99%
“…Besides, liver fibrosis can result in changes in hepatic microcirculation and perfusion. Fan et al [ 84 ] found that MR perfusion parameters, time to peak, and mean transit time in particular could reflect the degree of liver fibrosis. Similarly, Yoon et al [ 85 ] also found that portal blood flow was significantly lower in clinically significant hepatic fibrosis and that mean transit time and extracellular volume increased in cirrhosis.…”
Section: Progression Of Diffuse Liver Diseasementioning
confidence: 99%